The Role of Pancasila and Citizenship Education in Counseling Guidance - Sumarni Sumarni; Devina Amalia (Edumaspul: Jurnal Pendidikan, 2022)
Pancasila and citizenship education are subjects that are used as a vehicle to develop and preserve noble and moral values rooted in the culture of the Indonesian nation. This study aims to determine the role of Pancasila and citizenship education in counseling guidance. The research method used is a literature review using the Google Scholar search engine with a total of 62 articles. The results obtained 8 articles that have met the inclusion and exclusion criteria about the role of Pancasila and citizenship education in counseling guidance. The results of the research that look at the scope show that Pancasila and civic education in counseling guidance can improve the character development of students, can instill a high spirit of nationalism and love for the homeland, and from this high spirit of nationalism, quality human resources are born for the development of the nation and state.